The Effect of Socio-Cultural Diversity on Knowledge Sharing - Okyere-Kwakye, Eugene; Nor, Khalil Md (Advances in Social Sciences Research Journal, 2016)
Knowledge sharing, perhaps knowledge management tops the headlines of todays’ organizational news. As the old adage goes “knowledge cannot be found in one man’s head”; therefore, employees should share their knowledge. While individuals in organizations might be cognizance with the strength in diversity and the significance of sharing their experiences, it is no news that employees loath the act of sharing their knowledge especially to people of different social group. This issue has been examined by many researchers. As the behavior individuals’ exhibit in varied circumstances hinges greatly on the social environment in which they find themselves, their level of participation or willingness towards sharing knowledge might also not be different. Thus, we hypothesize those certain socio cultural factors: nepotism, tribalism, openness to diversity and cronyism may have influence on individuals’ knowledge sharing behavior.